Administrating Kinship: Marriage Impediments and Dispensation Policies in the 18th and 19th Centuries - Lanzinger, Margareth (Brill, 2023)
From the late eighteenth century, more and more men and women wanted to marry their cousins or in-laws. In this case, bridal couples had to apply for a papal dispensation and this meant a hurdled, lengthy and also expensive procedure. This book shows that applicants in four dioceses - Brixen, Chur, Salzburg and Trent - took very different paths through the thicket of bureaucracy to achieve their goal.